Pergeseran Bentuk dan Makna Terjemahan dalam Cerpen Kappa Karya Akutagawa Ryunosuke - Krisna P, Ni Putu Ayu (Humanis, 2018)
This research focuses on the analysis of shifting in form and meaning of short story entitled Kappa from Japanese into indonesian. The purpose of this research is to know the translation in form and meaning and also the technique used by the translator in the alignment of the form and the meaning of the source in the context of the target. The data in this research are all words and sentences in Kappa short story by Akutagawa Ryunosuke and its translation in Indonesian with the same title translated by Winarta Adisubrata.The data were collected by referring method and technique of record, after that to analyze the data using method of translational pad with glossing technique then continued with formal and informal method in presenting the data. The theory used in this research are Catford shape shift theory (1965), theory of component analysis of meaning of Bell (1993) and technique theory of translation of Molina and Albir (2002). The result of this research shows that there are from 72 data of word class shift there are 24 data shift of verbs, 10 data shift of adjective, 27 data shift of adverb and 11 data shifting of noun and there are 10 data of meaning shift. The most widely used translation technique is literal translation technique.